Finite simple groups with Hall $\{2, r\}$-subgroups, $r \in π(G) \backslash \{2, t\}$, $t \in π(G) $ - Bashun, S. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.542 We describe finite simple groups with Hall biprimary subgroups of even order that contain Sylow subgroups of odd order of the $G$-group, except one of Sylow's subgroups of odd order.